KEPEMIMPINAN NON MUSLIM DALAM SYARIAH ISLAM - Tanjung, Sukran (UIN Sumatera Utara Medan, 2024)
Leadership in Islam is an urgent matter. When the Prophet Muhammad (peace be upon him) passed away, the first action taken by his companions was to choose a leader to succeed him—not as a prophet or messenger, but as a caliph to lead the community. The governance of a state in accordance with Islamic law, the enforcement of justice without discrimination, all depend on the leader. Thus, choosing a leader is not a trivial or easy matter, especially when the leader is a non-Muslim or disbeliever, while the majority of the people being led are Muslims. Sheikh Yusuf Qaradawi stated in his Contemporary Fatwas that when someone casts their vote for a leader, they are essentially testifying that the person is qualified to lead the Muslim community. This choice will be held accountable by Allah Almighty on the promised Day of Judgment.